2014
DOI: 10.3390/ijerph110403678
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Green Exercise on Blood Pressure, Heart Rate and Mood State in Primary School Children

Abstract: The aim of this study was exploratory and sought to examine the effect on blood pressure (BP), heart rate (HR) and mood state responses in primary school children of moderate intensity cycling whilst viewing a green environment compared to exercise alone. Following ethics approval and parental informed consent, 14 children (seven boys, seven girls, Mean age ± SD = 10 ± 1 years) undertook two, 15 min bouts of cycling at a moderate exercise intensity in a counterbalanced order. In one bout they cycled whilst vie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
93
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(96 citation statements)
references
References 36 publications
2
93
0
1
Order By: Relevance
“…Two studies applied experimental approaches to examine the association between short-term exposure to simulated green spaces and blood pressure after short bouts of physical activity (83, 84), and found that subjects viewing videos of green, natural spaces had small reductions in blood pressure compared to those viewing urban scenes.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies applied experimental approaches to examine the association between short-term exposure to simulated green spaces and blood pressure after short bouts of physical activity (83, 84), and found that subjects viewing videos of green, natural spaces had small reductions in blood pressure compared to those viewing urban scenes.…”
Section: Introductionmentioning
confidence: 99%
“…As antidote to issues of urbanization which put adolescents 'at-risk' , outdoor programs using adventure activities have been suggested to build resilience and well-being (Ungar, Dumond, & McDonald, 2005). The physical self, the second of the three core elements, is the easiest to describe and support empirically; the physicality of outdoor travel and living is inherent and obvious, and the research on the benefits of physical exercise, especially in the context of 'green' or outdoor exercise, is growing rapidly (Barton & Pretty, 2010;Duncan et al, 2014). Green exercise has been found to improve mood states and positive engagement, reduce tension, confusion, anger and depression, and increase energy (Thompson Coon et al, 2011).…”
Section: Key Practices and Core Theoretical Elements Of Wilderness Thmentioning
confidence: 99%
“…Nor did we find information about the impact of playing in natural environments on gross motor skill development. With a growing literature highlighting the short [29,30,31] and longer-term importance of motor skill development [32] and a child’s micro environment to PA (particularly school grounds) [33,34,35], as well as the importance of exposure to nature to mental and physical well-being [36], we felt it was important to determine whether children were being exposed to natural features at their elementary schools and to assess whether these natural features afforded opportunities for motor skill development. …”
Section: Discussionmentioning
confidence: 99%